2009
DOI: 10.1186/1471-2180-9-79
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer isolate PT3, super-permissive for adeno-associated virus replication, over-expresses DNA polymerase δ, PCNA, RFC and RPA

Abstract: BackgroundAdeno-associated virus (AAV) type 2 is an important virus due to its use as a safe and effective human gene therapy vector and its negative association with certain malignancies. AAV, a dependo-parvovirus, autonomously replicates in stratified squamous epithelium. Such tissue occurs in the nasopharynx and anogenitals, from which AAV has been clinically isolated. Related autonomous parvoviruses also demonstrate cell tropism and preferentially replicate in oncogenically transformed cells. Combining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Additionally AAV2 is known to autonomously replicate in differentiating skin cells [12][15]. We therefore utilized the organotypic epithelial raft culture system (skin raft) to analyze effects of X on AAV2 autonomous DNA replication.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally AAV2 is known to autonomously replicate in differentiating skin cells [12][15]. We therefore utilized the organotypic epithelial raft culture system (skin raft) to analyze effects of X on AAV2 autonomous DNA replication.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing three primary isolates and two established cervical cancer cell lines to normal keratinocytes Kang et al could detect overexpression of RPA, RFC, PCNA and DNA polymerase, which seem to play a role in adeno-associated virus DNA replication. 63 Increased expression of sine oculis homebox homologue 1 (SIX1, a master regulator of DNA replication in cervical cancer cells) can be induced by the E7 oncoprotein of HPVs in cervical intraepithelial neoplasia and cervical cancer and can result in higher levels of expression of genes related to the initiation of DNA replication such as RFC4. 69 Recently Niu et al showed that dysregulation of CDKN2A, IL1R2 and RFC4 may contribute to cervical cancer progression and may be potential diagnostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of DNA polymerase δ-associated factors could explain the reduced conversion of incoming virus DNA in bovine cells, as these cellular components are known participants in initial replication of parvovirus genomes. Increased expression of proliferating cell nuclear antigen in certain cervical cancer isolates has been shown to enhance DNA replication of the parvovirus adeno-associated virus (Kang et al , 2009), suggesting that the expression level of these factors can alter parvovirus permissivity.…”
Section: Discussionmentioning
confidence: 99%